A study of self-vetoing balloon vessel for liquid-scintillator detectors. Issue 1 (1st November 2022) - Obara, S.; Gando, Y.; Ieki, S.; Ikeda, H.; Ishidoshiro, K.; Nakamura, R.; ,
Abstract : KamLAND-Zen searches for neutrinoless double-beta decay with an ultra-pure liquid-scintillator (LS) filled with a custom-made clean nylon balloon. The primary backgrounds are radioactive impurities such as uranium and thorium series. To reduce them, we studied a self-vetoing balloon-shaped vessel for a future upgrade program, "KamLAND2-Zen". We selected Polyethylene-Naphthalate (PEN) film which emit fluorescent light and performed the feasibility studies. Owing to its scintillation properties, 214 Bi background could be identified in the KamLAND2-Zen. Moreover, thanks to the different waveforms between the LS and the PEN, we can apply the pulse-shape-discrimination for 212 Bi-Po pileup background. We evaluated its background rejection efficiency as more than 90%. Resulting from these studies, it is possible to remove restrictions on fiducial volume in KamLAND2-Zen.